Editorial - Kelly R. Maguire; Scott W. Greenberger (Journal of Scholarly Engagement)
The Journal of Scholarly Engagement kicked off the 2022 year with a (virtual) annual meeting with the Editorial Board. Joining our board as new members this year include Drs. Laura Cruz, Kelvin Thompson, and Sandi van Lieu. We are grateful for the board’s continued support, expertise, and feedback on how to further enhance the awareness of the Journal of Scholarly Engagement for faculty researchers and general scholars within the field of Boyer studies.